2011
DOI: 10.1039/c1cc13348a
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic intermolecular allyl–allyl cross-couplings between alcohols and boronates

Abstract: We developed catalytic intermolecular C(sp(3))-C(sp(3)) cross-couplings between various allyl alcohols and allyl boronates, which proceeded smoothly in the presence of nickel(0) under mild conditions to form 1,5-dienes with excellent linear- and γ-selectivity; the use of boronates proved to be crucial in terms of reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The results indicated that the Lewis acidic features of organoboronic acid derivatives are required for this reaction. Allylic alcohol may be activated by the coordination with arylboron compounds [9] or forming a boronate [14] to facilitate the oxidative addition step. It should be noted that the coupling methods that could accommodate both organoboronic acid and other boron regents are quite rare.…”
Section: Concise Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that the Lewis acidic features of organoboronic acid derivatives are required for this reaction. Allylic alcohol may be activated by the coordination with arylboron compounds [9] or forming a boronate [14] to facilitate the oxidative addition step. It should be noted that the coupling methods that could accommodate both organoboronic acid and other boron regents are quite rare.…”
Section: Concise Reportmentioning
confidence: 99%
“…In 2011, Kobayashi and coworkers developed a nickel-catalyzed allyl-allyl cross-couplings between alcohols and allyl boronates. [9] However, no allyl-aryl crosscoupling via reactions with arylboron reagents was described in this paper. In addition, Ni(cod) 2 was ineffective for this reaction.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Leboeuf 4 ,e ntry 15). [12] Finally,t he reaction was attempted with (E)-styrylsilane 2e,asubstrate that has already been used by Niggemann et al for af ew calcium-catalyzed alkenylation of alcohols.…”
mentioning
confidence: 99%
“…More recently, allylic boronates have been used as partners for cross-coupling reactions with aryl 6 and allyl electrophiles. 7 Due to the importance of allylboronate building blocks in synthetic organic chemistry, their synthesis has been the subject of many studies. Besides stoichiometric substitution reactions that involve allyllithium 8 or allylmagnesium 9 reagents, homologation of vinyl boronates 10 has also been a practical route to many of these materials.…”
mentioning
confidence: 99%